Dialogue Summary: Measuring Health System Efficiency in Canada - Lavis, JN (My University, 2011)
A summary of what was learned from a stakeholder dialogue that addressed problems related to measuring health system efficiency, options for addressing these problems, key implementation considerations, and next steps for measuring health system efficiency in Canada.
Keywords: health system; efficiency; Canada